2022
DOI: 10.1051/matecconf/202237009008
|View full text |Cite
|
Sign up to set email alerts
|

Structural and mechanical properties of monazite type LnPO4 (Ln = La, Ce, Pr and Nd)

Abstract: Monazite, as a source of raw materials, plays a significant role in the development and applications of green technologies, including medicine and energy production. It contains nuclear materials, which are challenging to extract by convectional cracking processes. However, a new method (thermal plasma cracking) has been proposed for processing monazite. The first principles calculation approach was used to investigate the theoretical structure and mechanical properties of monazite-systems to gain deeper under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…Previously, Monazite-La was investigated by a first-principles calculation based on density functional theory (DFT) at 0 GPa [6,7]. It was found that this system (Monazite-La) is mechanically stable and vibrationally unstable.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Monazite-La was investigated by a first-principles calculation based on density functional theory (DFT) at 0 GPa [6,7]. It was found that this system (Monazite-La) is mechanically stable and vibrationally unstable.…”
Section: Introductionmentioning
confidence: 99%